2020
DOI: 10.4000/irpp.1343
|View full text |Cite
|
Sign up to set email alerts
|

How ideas matter in public policy: a review of concepts, mechanisms, and methods

Abstract: The recent ideational turn in political science and public administration implies that ideas matter. Ideas are an essential explanatory concept for understanding policy changes and decisionmaking processes. The aim of the paper is to specify how ideas matter as a variable in public policy research, providing students and scholars of public policy with a stock take of the current state-of-the-art literature on ideas in political science and public administration. The paper first identifies three approaches to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 108 publications
0
34
0
1
Order By: Relevance
“…This area of studies originated from King (1973) and got a new impulse in the 1990s after Hall's pioneering studies (1989;. For the last few decades, this research has expanded signi cantly and now involves various social scientists, including institutionalists, constructivists, and rational choice scholars (Berman 2013;Hogan and Howlett 2015;Swinkels 2020). This eld examines how policy ideas are institutionalized and turn into policy instruments.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…This area of studies originated from King (1973) and got a new impulse in the 1990s after Hall's pioneering studies (1989;. For the last few decades, this research has expanded signi cantly and now involves various social scientists, including institutionalists, constructivists, and rational choice scholars (Berman 2013;Hogan and Howlett 2015;Swinkels 2020). This eld examines how policy ideas are institutionalized and turn into policy instruments.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…Furthermore, ideas about specific types of investment like CSLI are not easy to distinguish methodologically from related and more general ideas about foreign investment or the general 'investment climate' of an economy (see Linsi, 2020). We hence approach this interaction and co-constitution of material and ideational factors methodologically by integrating different methodological elements of ideational studies (Swinkels, 2020): By triangulating the textual data we gather from policy documents, newspapers, and reports with expert interviews, we ensure to adequately capture the nuances of these ideational changes. Our dependent variable -the changing investment regimes -adds further leverage to the argument, since these 'material' changes require a preceding change in the ideas and preferences of policy-makers.…”
Section: Methodsmentioning
confidence: 99%
“…The underlying idea is that objects of governance are hybrid, co-produced entities that emerge from complex interactions between expert knowledge, political interventions and mundane practices ( Allan, 2018 ). In other fields of research, it has already been demonstrated how epistemic communities play a central role in the development of new and altered policy ideas ( Swinkels, 2020 ). Examples of such research are: the climate as an object of (global) governance ( Bulkeley, 2005 ; Allan, 2017 ), urban warming as an object of (local) governance ( Boezeman and Kooij, 2015 ), or creative thinking as an object of governance and geopolitical concern in the United States military context during the Cold War ( Van Eekelen, 2017 ).…”
Section: Robots As Objects Of Future Governancementioning
confidence: 99%